The Relation Between Organizational Justice And Organizational Citizenship Behavior In Hospitals Of Tehran University Of Medical Sciences - Sodabe Vatankhah; Somaye Yegane; Taha Nasiri; Lida Shams; Golrokh Atighechian; Habibe Vazirinasab (Tehran University of Medical Sciences, 2014)
Background and Aim: Since employees satisfaction have important effects on achieving the goals of organizations and also organizational justice is a key factor in employees satisfaction, The aim of this study was to determine the relationship between organizational justice and organizational citizenship behavior in selected hospitals of Tehran University of Medical Sciences. Materials and Methods: This study was a descriptive and cross-sectional analysis. The study sample was composed of 312 employees from selected hospitals of Tehran University of Medical Sciences by cluster Stratified Random sampling. Data collected by using two questionnaires: Moorman& Niehoff Organizational Justice and Yaghoobi Organizational Citizenship Bahavior. The questionnaires reliability was supported and based on Cronbach s Alfa (OJ=94%, OCB=93%) and questionnaire validity was confirmed by specialist point of view. Data was analyzed by SPSS 18 software. Results: The result of analysis revealed that Hasheminejad hospital had the highest score of organizational citizenship behavior in all dimensions except for altruismin dimension. The score in each of the dimensions for organizational justice except for interactional justice in Hasheminejad hospital were the highest There was significant relationship between organizational justice and organizational citizenship behavior in the following dimensions: Altruism, Conscientiousness, Courtesy, Sportsmanship (p=0/0001).  Conclusion: As shown, there was a relationship between organizational justice and all aspect of organizational citizenship behavior in selected hospitals and also there was a positive relationship between involving staffs in organizationl activities with facilitating achievement of organizational goals and improvement of hospital performance, Therefore, strategies should be adopted in line with organizational justice to increase citizenship behavior.